The Czech and Slovak Federal Republic : An Economy in Transition: Occa Paper No.72. (Occasional Papers; Occasional Paper, 1990)
This paper is based on an internal report prepared by the IMF staff in connection with the application of the Czech and Slovak Federal Republic (Czechoslovakia) for membership in the IMF. The paper surveys the economic system that had developed up to the time of the reforms begun in 1987 and outlines the economy's performance during 1945-1985. It then discusses the economic developments of 1985-1990, with separate sections on output, prices, public finance, money, and the balance of payments. Prices served mainly as an instrument of central planning: each price was set independently and a change in one price had no influence on other prices. The annual foreign exchange plan, derived from the state plan, strictly controlled foreign exchange transactions. It specified imports and exports of goods and services by enterprises for the convertible and nonconvertible area. The exact modalities of the denationalization scheme have not yet been determined. However, consideration is being given to a scheme whereby state enterprises would be transformed into joint stock companies, and 'ownership vouchers' would be distributed to the population which would entitle their holders to purchase stock in these companies.